PENCEGAHAN PERKAWINAN ANAK MELALUI KONSELING SEBAYA - Rosdiana; Rusyaid; Darnanengsih (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Child marriage remains a serious challenge in Sorong Regency, impacting the health, education, and future prospects of adolescents. This community service aims to raise awareness among adolescents about preventing child marriage by training them to become peer tutors using the Participatory Action Research (PAR) approach. A total of 30 adolescents participated in the training and took pre- and post-tests to measure the effectiveness of the intervention. Analysis of the results showed a significant average increase, with scores rising from 6.87 on the pre-training test to 12.33 on the post-training test. Cohen's d value of 5.42 indicates a very large effect size, proving that the training increased participants' knowledge. The PAR approach strengthens adolescents' active participation in the learning process, enabling them to internalise the knowledge they gain. These findings confirm that the peer tutor model is an effective educational strategy in this context and can be recommended as a measure to prevent child marriage at community level. The programme also has the potential to be replicated in other areas with similar social characteristics.